2000
DOI: 10.1139/f00-204
|View full text |Cite
|
Sign up to set email alerts
|

Interpopulation differences in growth rates and food conversion efficiencies of young Grand Banks and Gulf of Maine Atlantic cod (Gadus morhua)

Abstract: Geographically separated Atlantic cod (Gadus morhua) stocks in the northwest Atlantic exhibit life history variation and have been shown to differ genetically. The genetic and environmental contributions to phenotypic differences, however, have not yet been measured. We used common environment experiments to evaluate the importance of temperature on the observed growth variation between Grand Banks (GB) and Gulf of Maine (GOM) cod stocks. Larvae from the GB grew faster than GOM larvae at both 7 and 12°C. Growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 22 publications
3
46
0
Order By: Relevance
“…, which agrees well with growth rates obtained in other laboratory studies using age-0 juvenile cod (Brown et al 1989, Folkvord & Otterå 1993, Otterlei 2000, Purchase & Brown 2000. For example, a G max of ~2.6 % d -1 was observed for 0.9 to 9.2 g juvenile cod feeding maximally at 9.5°C (Folkvord & Otterå 1993).…”
Section: Rates Of Food Consumption and Growthsupporting
confidence: 91%
See 1 more Smart Citation
“…, which agrees well with growth rates obtained in other laboratory studies using age-0 juvenile cod (Brown et al 1989, Folkvord & Otterå 1993, Otterlei 2000, Purchase & Brown 2000. For example, a G max of ~2.6 % d -1 was observed for 0.9 to 9.2 g juvenile cod feeding maximally at 9.5°C (Folkvord & Otterå 1993).…”
Section: Rates Of Food Consumption and Growthsupporting
confidence: 91%
“…Edwards et al 1972, Jones 1978, Jones & Hislop 1978, Hawkins et al 1985, relatively little research has been conducted on this relationship in age-0 juvenile cod. Our understanding of the growth-feeding relationship in age-0 juvenile cod has been advanced by studies conducted at cold temperatures (Brown et al 1989) and maximal feeding levels (Otterlei 2000, Purchase & Brown 2000. Extending these analyses to include a wider range in both temperatures and feeding levels would provide additional ecologically relevant data, since age-0 juvenile cod are found over a wide temperature range (Fahay et al 1999) and feeding may be sub-maximal due to limited prey resources (Buckley et al unpubl.…”
Section: Introductionmentioning
confidence: 99%
“…Conover & Schultz 1995), it has been reported for several species including turbot (Scophthalmus maximus; Imsland et al 2001) and cod from separate populations on the coast of Canada (Purchase & Brown 2000). In the study of Purchase & Brown (2000), strains were kept in separate tanks and fed to satiation, thus reducing the need for competition. In the present study the focus was on behavioural adaptations of the strains.…”
Section: Gross Food Conversion Efficiencymentioning
confidence: 99%
“…Populations in warm water grow faster and mature earlier than those in colder water (Hutchings et al 1993, Brander 1994b. Previous studies have reported photoperiod affecting growth in cod larvae, with those in northern latitudes having a longer time for visual feeding during summer (Suthers & Sundby 1996), and higher food-conversion efficiency in northern cod compared with southern cod off the coast of Canada (Purchase & Brown 2000). Some of the units are heavily overfished and have collapsed; they have shown slow recovery even under a complete fishing moratoria (Hutchings 2000).…”
Section: Introductionmentioning
confidence: 99%
“…growth rate) have successfully been used to test CnGV theory in fish populations (Conover & Schultz 1995). However, in Atlantic cod, studies of CnGV theory have been limited to 2 populations (Svåsand et al 1996, Otterlei et al 1999, Purchase & Brown 2000a,b, Salvanes et al 2004). Marcil et al (2006a) showed that laboratory reared juvenile cod from 2 regions of the NW Atlantic, 4X and 3L (Northwest Atlantic Fisheries Organization [NAFO] divisions), differed significantly in their body shape, yet no differences were found between the wild collected juveniles of the same origin.…”
Section: Introductionmentioning
confidence: 99%